Compare of Food Habit and Nutritional Status of Rural Male and Female: Food habitat and Nutrition - rahman, redwan; Sheema , Mahfuza Khanom (Advances in Social Sciences Research Journal, 2021)
ABSTRACT There is a big difference between male and female in the rural environment of Bangladesh and the aim of this eating habits and nutritional status. The study was conducted through 384 respondents from 9 villages in Ishwardi, Pabna; a north-western district of Bangladesh. The research has done on the food habits of the middle and lower class people of the villages. And some informations are collected from the different sources. In the research 73.44% of male earn more than 24 thousand BDT per month when only 43.32% female are earning more than 24 thousand BDT. Most of the female are housewives and male are service holder. 44.79% male are service holder on the other hand 4.69% female are service holder. Rice is the main food for Bangladesh. So, most of the people have rice on daily three times. 37.80% of female and 66.98% of male are having rice. Ruti is the second priority food, female take this food 0.56% and male take 7.55% for 2 days. 63.33% female take egg, on the other hand 58.07% male take egg per week. 3.2% female her meal last of all and 1.5% female take it first of all. On the other hand 6.25% male take their meal first of all and 3.39% male take their meal last of all. Most of the female are normal having BMI 89.06% on the other hand male are overweight 78.18%. In the light of the study the eating habits of male and female in Bangladesh have improved but it has not yet affected everyone.